Suomalaisen käännöstieteen näkyvyys maailmalla Tarkastelussa kuusi kansainvälistä käännöstieteen lehteä vuosilta 1966–2020 - Taivalkoski-Shilov Kristiina (Suomen kääntäjien ja tulkkien liitto, 2022)
The history of Translation Studies in Finland is still largely unstudied. Particularly little research has so far been done on scholarly publishing. The well-known exception to the rule is Gideon Toury (2009), who when studying the statistics of the prestigious journal Target from its first twenty years (1989–2008), observed that Finland was among the major contributing countries and thus a central country on the map of Translation Studies. This paper investigates what happened to Finland’s centrality in Target during 2009–2020, albeit with different methods. Furthermore, the analysis has been extended to five other well-known journals: Meta, Perspectives, The Trans-lator, trans-kom and Translation Studies, in order to study Finland’s visibility in Translation Stud-ies on a larger scale. The analysis shows changes in the proportions of contributing countries in Target. Scholars with a Finnish affiliation represented only 3 per cent of all (co-)authors 2009–2020. However, when multiple appearances are calculated the proportions are slightly different, and Finland ranks ninth with Canada among the ten most contributing countries to Target. As to the other journals, Finnish scholars have a visible position (8 per cent of all authors) only in trans-kom, whereas in the four other journals, they represent 1–3 per cent of all contributors.